Goldilocks: American precious metals and the Rise of the West - Yao Chen; Nuno Palma; Felix Ward (Tinbergen Institute, 2022)
We estimate the contribution of the American precious metal windfall to West Europe's growth performance in the early modern period. The exogenous nature of American money arrivals allows for identification of monetary effects. We find that more than half of West Europe's growth can be attributed to American precious metals, whose arrival promoted trade intensification and capital formation. Our findings place West Europe's second-stage receivers in a particularly fortunate goldilocks zone that enjoyed monetary injections, while being insulated against the transport-loss induced financial crises that caused persistent damage to first-stage receiver Spain.
Keywords: E51; F40; N10; 330; Money non-neutrality; Great Divergence; Little Divergence; Smithian growth; market integration